Thermodynamics and non-isothermal kinetic modelling of CoAl2O4 conversion from cobalt-aluminium complexes - Dumanli, Fatma Tugce Senberber; Derun, Emek Moroydor (ELSEVIER, 2024)
Spinel compounds, classified as ceramics, have exhibited excellent industrial application features. The spinel form of cobalt aluminate was successfully synthesized by using the co-precipitation method. A comprehensive explanation of spinel cobalt synthesis was provided, including thermodynamics and non-isothermal kinetic modelling of the transformation process of cobalt-aluminium complexes into CoAl2O4. The synthesized bluecoloured powder was identified as Spinel (CoAl2O4) with the cubic crystal system. In the morphological analyses, particle sizes were varied in the range of 130-250 nm. The CoAl2O4 formation was explained by a threestep reaction and the Coast-Redfern non-isothermal kinetic method. The averages of activation energies were found as 53.42 kJ/mol, 56.19 kJ/mol and 380.25 kJ/mol for the first, second and third steps of the thermal process, respectively. The synthesis reaction was found to be endothermic and non-spontaneous based on calculations of thermodynamic functions of Delta H, Delta G, and Delta S by using activated complex theory.
Keywords: Cobalt aluminate; Spinel; Thermal decomposition; Thermodynamic; X-ray methods; PERFORMANCE; PARTICLES; Physics